Improvisation as a Meta-Counseling Skill. Issue 1 (2nd January 2017) - Farley, Ned
ABSTRACT: Counselor education tends to see the development of basic counseling and communication skills as the foundation of clinical training. Improvisation has historically and primarily been connected to theater training and as a performance mechanism. By developing skills in spontaneity and the nature of narrative (or story) one becomes more able to be in-the-moment with a client or clients and thus less anxious and more able to meet the client where they are. As such, improvisation can really be seen as a meta-counseling skill—a skill that can form a firmer foundation for the learning of the basic counseling and communication micro-skills. This article outlines the core concepts of improvisational training for counselors and includes examples of improvisational games that can specifically help in preparing counselor trainees for their future clinical work.